Politics in the developing world a concise introduction - Haynes, Jeffrey (Malden, Blackwell Publishers, 2002)
Purposefully written for those coming to politics for the first time, this textbook provides an exploration and analysis of the most important political issues affecting the Developing World. Offering a different perspective from standard texts in this field, "Politics in the Developing World" encourages an understanding of the breadth and nature of a range of pressing - and previously understated - issues: the striving for democracy; the political consequences of economic growth and development; the struggle of religious and ethnic minorities; women's and human rights; the impact of globalization; and the politics of the natural environment.In doing so, the interaction of domestic and global factors affecting many of the Developing World countries is highlighted and a new qualitatively different set of concerns is identified. Some have resulted from recent international changes following the demise of the soviet bloc, including the shift to democracy in South Africa, and the ramifications of the late 1990s South East Asian financial crisis. To illustrate the importance of these themes and issues five Developing World regions are focused on and explored in detail: Latin America and the Caribbean, South Asia, East and South East Asia, the Middle East and North Africa, and sub-Saharan Africa.While based on Haynes' previous publication, "Third World Politics: A Concise Introduction" (1996), this is a new book, completely rewritten, with updated regional analyses and data throughout. It focuses upon changes in the Developing World in the last decade, with an increased focus on its international relations, complementing those chapters concerned with domestic issues. An ideal introduction and an invitation to further study, this text is essential reading for introductory students studying a range of courses including development studies, global politics, world politics, Developing World politics, comparative politics, and international relations.
Includes bibliographical references (p. [276]-291) and index.
Keywords: Globalization